PENGARUH PENAMBAHAN LIMBAH SERBUK CANGKANG KERANG DAN SERBUK KACA SEBAGAI BAHAN PENGGANTI SEMEN TERHADAP KUAT TEKAN BETON NORMAL - Nurjanah Nurjanah; M. Dani Juli Rohman; Riski Krisdiantoro (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
Abstrac This research was conducted to determine the effect of the addition of waste shells and shell powder glass powder on the compressive strength of concrete. The method used is to use the experimental method by making test specimens with a mixture of waste shells powder shells and glass powder by 4%; 8%; 12% then compared with normal concrete without added ingredients. Concrete specimens that have been soaked then tested their compressive strength with the age of 7 days, 14 days, 21 days, and 28 days. The results of the test showed that normal concrete which was not added with the waste of shell powder and glass powder had compressive strength under mixed concrete variations of 4%, 8%, and 12 % when the concrete was 28 days old. Concrete which is added with waste of shell powder and glass powder has a high yield at 4% variation that is equal to 20,66 MPa. For concrete Variasi of 8% has a compressive streng value of 20,17 MPa, For variations of 12% has a compressive strength value of 20,46 MPa and for normal concrete has a compressive strength of 20,16 MPa at the age 28 days. The compressive strength value generated by the research that occurs due to the slump test value factor that is done is not the same. Keywords: Concrete, scallop waste powder, Glass powder waste, concrete compressive strength.